Buccofacial apraxia in primary progressive aphasia. (January 2023) - Morihara, Keisuke; Ota, Shoko; Kakinuma, Kazuo; Kawakami, Nobuko; Higashiyama, Yuichi; Kanno, Shigenori; Tanaka, Fumiaki; Suzuki, Kyoko
Abstract: Buccofacial apraxia (BFA) is associated with nonfluent/agrammatic variant primary progressive aphasia (nfvPPA) as well as with the severity of apraxia of speech (AOS), a core symptom of nfvPPA. However, an association with agrammatism has not been established. The aim of this study was to examine the association between BFA and agrammatism in nfvPPA and to determine differences in atrophic regions in primary progressive aphasia (PPA) with and without BFA. Seventy-four patients with PPA were recruited, including 34, 15, 10, and 15 patients with nfvPPA, semantic variant PPA, logopenic variant PPA, and unclassified PPA, respectively. All patients underwent language examination and BFA evaluations. Voxel-based morphometry (VBM) was performed to determine whether atrophy of a specific lesion correlated with the presence of BFA. BFA was observed in 20 and 3 patients with nfvPPA and unclassified PPA, respectively. In a comparison of patients with nfvPPA with and without BFA, the BFA group showed significantly worse spontaneous speech and writing in the Western Aphasia Battery. The agrammatism ratio or the ratio of agrammatic errors to the total number of particles was higher in the BFA group; however, the severity of prosodic and phonetic components of AOS did not differ between the two groups. VBM showed that the severity of BFA correlated with atrophy of the opercular and triangular areas of the inferior frontal gyrus to a part of the left middle frontal gyrus. BFA has a different anatomical basis from AOS in patients with nfvPPA and that BFA is characterized by more anterior degeneration compared to that of AOS.